Exclusive Breastfeeding and Gross Motor Development in Six-Month-Old Infants: A Cross-Sectional Study at Manyar Primary Health Center, Gresik Regency - Nanik Nuraini; Yuyun Farihatin; Abdul Muhith (Universitas Ibn Khaldun Bogor, 2026)
Background: Gross motor development in six-month-old infants is strongly influenced by nutritional adequacy during early life. Exclusive breastfeeding provides complete nutrition including DHA, AA, enzymes, and antibodies that support neuromuscular development. Objective: This study aimed to analyze the relationship between exclusive breastfeeding and gross motor development in six-month-old infants at Manyar Primary Health Center, Gresik Regency. Methods: This study employed an observational quantitative approach with a cross-sectional design. Purposive sampling was used to recruit 30 mothers with six-month-old infants. Data were collected using a breastfeeding status questionnaire and the Pre-Screening Developmental Questionnaire (KPSP) appropriate for six months of age. Data analysis was performed using the Chi-square test and Fisher's exact test. Results: Of 30 infants, 23 (76.7%) received exclusive breastfeeding and 23 (76.7%) achieved appropriate gross motor development. Among exclusively breastfed infants, 91.3% demonstrated appropriate KPSP scores, compared to only 28.6% among non-exclusively breastfed infants. Statistical analysis revealed a significant association between exclusive breastfeeding and gross motor development (Fisher's exact p = 0.003; Odds Ratio = 26.25). Conclusion: Exclusive breastfeeding is significantly associated with appropriate gross motor development in six-month-old infants. Healthcare providers should strengthen breastfeeding education and early developmental stimulation programs to optimize infant growth outcomes.